Pattern and factors associated with home accidents among under-five children and its care seeking behavior in selected rural communities of Kota samarahan district, Sarawak, Malaysia - Hann, Lim Jyh; Rahman, Md Mizanur (Bangladesh Journal of Medicine, 2018)
Background: Home may beconsidered a place toescape the dangers of theoutside world. Children have the highest risk for home injury and accidents. Considering this view, this study was aimed to describe the pattern of home accidents among the under-five children in selected villagesin Kota Samarahandistrict andto determine their care-seeking behavior. Materials and Methods: This was a cross-sectional study conducted in four villages in Kota Samarahan district. A total of 917 households were visited. Among them, 261 households were having under five children. Out of 261 households, 248 had completed the interview with the response rate of 95%. Data was collected from caregivers of under-five children by face to face interview by interviewer-administered questionnaire. Data entry and analysis was done by IBM SPSS version 22.0. A p-value less than 0.05 wasconsidered as statistically significant. Results: The prevalence of home accident was 68.1% in thelast six months. Two-fifths (40.3%) of the households had at least one incidence of home accidents. The most common home accidents were fall (56.9%) followed by cut/ wound (16.9%) and struck by an object (10.5%). Logistic regression analysis revealed that age, marital status and household income appeared to be important predictors of home accidents among under-five children (p<0.05). More than half of the respondents took home treatment for accidents such as fall, cut/ wound, struck by an object and insect bites. While all who suffered from severe home accidents such as poisoning, suffocation and vehicle accidents would visit the nearest healthcare facilities for treatment. Conclusion and Recommendation: A comprehensive and preventive program could be implemented involving the vulnerable segments of the population and emphasise on most common home accidents as in the study findings. Bangladesh J Medicine Jul 2017; 28(2) : 58-62